IImplementasi Strategi Keunggulan Biaya dalam Usaha Express Laundry Purwakarta - Zain, Anisa Raihan Fadhilah; Khofifah, Nisa Nurramdhiani; Bahrun, Adriansah (ECONBANK: Journal of Economics and Banking, 2021)
The number of businesses in laundry resulted in the number of competitors getting tougher. One of the management strategies that can be applied in creating and increasing competitive advantage is to implement a cost advantage strategy. This study aims to determine the cost advantage strategy in the Express Laundry business in Purwakarta. Data collection techniques in this study by conducting direct observations in the field and interviews with informants in accordance with the problems studied. The type of research used is descriptive qualitative. The result of this research is the implementation of a cost advantage strategy in the laundry business, Express Laundry provides quality products at low prices to be an attraction for customers. Armed with good service and affordable service prices, this business can have high market potential. Good service quality from a laundry or laundry business is the most important thing in providing satisfaction to customers. Keywords: Cost Advantage, Laundry Business, Express Laundry